Synthesis of Cu2PO4OH hierarchical superstructures with photocatalytic activity in visible light - Cho, In-Sun; Kim, Dong Wook; Lee, Sangwook; Kwak, Chae Hyun; Bae, Shin-Tae; Noh, Jun Hong; Yoon, Sung Hun; Jung, Hyun Suk; Kim, Dong-Wan; Hong, Kug Sun (WILEY-V C H VERLAG GMBH, 2008)
Using a wet-chemical method and without any surfactants or templates, various 3D hierarchical superstructures of Cu2PO4OH were synthesized by simply adjusting the pH. The resulting hierarchical superstructures were characterized using X-ray diffraction (XRD), field-emission scanning electron microscopy (FESEM), high resolution-TEM (HRTEM), Fourier transform infrared spectroscopy (FTIR), Raman, and UV-Vis spectroscopy. With an increase in pH from 2.5 to 7.0, the morphology of Cu2PO4OH varied from microrods to walnut-shaped microspheres of self-assembled nanoparticles. A possible mechanism for the formation of the Cu2PO4OH hierarchical superstructures was also proposed. The optical properties of the Cu2PO4OH hierarchical superstructures were strongly related to their morphologies and the size of the assembled crystallites. We further demonstrated the useful photocatalytic activity of these complex structures in the degradation of methylene blue (MB) dye under visible light irradiation (lambda > 410 nm). The best photocatalytic performance was achieved by Cu2PO4OH with a walnut-shaped morphology due to the excellent absorption of visible light as well as a high BET surface area.
Keywords: COPPER HYDROXYPHOSPHATE; NANOCRYSTALS; CU-2(OH)PO4; PHOSPHATES; OXIDATION; SYSTEM; OXYGEN